Mutational spectrum of the TYR and SLC45A2 genes in Pakistani families with oculocutaneous albinism, and potential founder effect of missense substitution (p.Arg77Gln) of tyrosinase. (1st October 2015) - Shah, S. A.; Raheem, N.; Daud, S.; Mubeen, J.; Shaikh, A. A.; Baloch, A. H.; Nadeem, A.; Tayyab, M.; Babar, M. E.; Ahmad, J.
Summary: Background: Oculocutaneous albinism (OCA) is an autosomal recessive disorder of abnormal melanin formation, which results in hypopigmentation of skin, hair and eyes. OCA is classified into four types based on clinical and genetic findings. OCA1 is the most severe form of albinism, and is caused by mutations in the tyrosinase ( TYR ) gene, while OCA4 is caused due to mutations in SLC45A2 . Methods: In total, 13 families with ≥ 3 members with OCA were enrolled. Family history was ascertained and pedigrees were drawn up. Blood samples were collected and processed for DNA extraction. Linkage analysis was performed by typing three short tandem repeat markers in candidate regions of TYR and SLC45A2 . Sequence analysis was performed of all the coding exons and adjacent intronic sequences of both genes. Results: Eight families showed linkage to OCA1 and one family showed linkage to OCA4 . Four missense substitutions (p.Arg239Trp, p.Ser192Tyr, p.Ser44Arg and p.Arg77Gln) were identified in TYR in the families with OCA1 linkage, and another missense substitution (p.Gln272Lys) was identified in the family with OCA4 linkage. One of the identified missense substitution (p.Arg77Gln) in TYR was found in five different families, which had a common haplotype. Conclusions: We identified four missense substitutions in TYR and a single missense substitution in SLC45A2 . One missense substitution (p.Arg77Gln) in TYR was found in five different families that originated from the same geographical area and displayed a common haplotype, suggesting a single origin that then spread to different geographical areas of Azad Kashmir, Pakistan.